Sterically Demanding Flexible Phosphoric Acids for Constructing Efficient and Multi‐Purpose Asymmetric Organocatalysts. (26th April 2022) - Scharinger, Fabian; Pálvölgyi, Ádám Márk; Weisz, Melanie; Weil, Matthias; Stanetty, Christian; Schnürch, Michael; Bica‐Schröder, Katharina
Abstract: Herein, we present a novel approach for various asymmetric transformations of cyclic enones. The combination of readily accessible chiral diamines and sterically demanding flexible phosphoric acids resulted in a simple and highly tunable catalyst framework. The careful optimization of the catalyst components led to the identification of a particularly powerful and multi‐purpose organocatalyst, which was successfully applied for asymmetric epoxidations, aziridinations, aza‐Michael‐initiated cyclizations, as well as for a novel Robinson‐like Michael‐initiated ring closure/aldol cyclization. High catalytic activities and excellent stereocontrol was observed for all four reaction types, indicating the excellent versatility of our catalytic system. Furthermore, a simple change in the diamine's configuration provided easy access to both product antipodes in all cases. Abstract : The ability of counterion enhanced catalysis to promote the asymmetric functionalization of enones was demonstrated. Combining the use of sterically demanding phosphoric acids with simple chiral diamines allowed for the preparation of simple ion‐paired and highly tunable organocatalysts. The latter could be applied in four different asymmetric transformations, providing a highly enantioselective access to both product antipodes in all cases.